TREATMENT OF GIANT DIAPHRAGMATIC HERNIA - V. V. Toidze; E. L. Vasyukova; V. A. Kashchenko; V. P. Akimov; A. M. Volkov (Вестник хирургии имени И.И. Грекова, 2018)
The authors demonstrate the results of treatment (16 patients) with giant paraesophageal and posttraumatic diaphragmatic hernia. The article represents the main principles of operation management, key moments of the choice of access, operative techniques and also the features of the usage of modern reticular implants.